THE STUDYING OF LEADERSHIP STYLES AND ALSO ITS INFLUENCE IN TERMS OF THE SUCCESS OF ORGANISATIONS: A PRACTICAL APPROACH - Sarvarjon Obidov (International Journal of Business, Law and Political Science, 2025)
Objective: This study investigates the impact of leadership styles on organizational success, emphasizing the roles and interpersonal dynamics of leaders in shaping managerial effectiveness. It aims to explore how transactional, transformational, and participative leadership styles influence organizational performance and address the need for reframing leadership practices to align with situational demands. Method: A mixed-method approach was employed. Primary data were collected using a quantitative survey with structured questionnaires administered to organizational leaders. Secondary data were obtained through an extensive literature review of studies on leadership styles and their organizational implications. Results: The findings reveal that adaptive leadership practices significantly enhance conflict resolution, stress management, and decision-making. Transactional, transformational, and participative leadership styles were shown to positively influence organizational outcomes. The research highlights the critical role of leaders in driving organizational success by aligning leadership strategies with evolving demands. Novelty: This study bridges theoretical frameworks and practical applications of leadership, offering a comprehensive perspective on how tailored leadership practices foster organizational adaptability and achievement of strategic goals. It provides actionable insights for enhancing leadership effectiveness in dynamic organizational settings.